Consultorio Jurídico gratuito de la Universidad de Otavalo. - Maldonado, Ximena E. (2019)
The linkage project Free Legal Clinic of the University of Otavalo It starts in the month of January of the year 2019 until November of the same year. The situation The initial phase of the project reflected difficulties in the management of the archive and in the distribution of the binding ones, as well as the physical space was not ideal for the attention required by users. A diagnosis of the situation described was made for what was executed an Improvement Plan for the operation of the Free Legal Clinic of the University of Otavalo, whose activities consisted of: 1. Equitable distribution of binding students per attorney from the Law Office and assignment of the tutor teacher, with their respective monitoring and follow-up. 2. According to the parameters established by the Public Defender's Office, the facilities to comply with the standards in their attention to care groups priority. 3. The active and passive file was restructured in order to systematize the information of the causes, in order to obtain statistics both in sponsorship and advice in the Family matters, Women. Childhood and Adolescence and Intrafamily Violence. 4. Several cases were reassigned to the student interns in order to follow up and quality service. 5. A proposed regulation was prepared that includes the requirements and attributions of the staff that is part of the Legal Clinic, which has been referred to the Regulations Commission of the University of Otavalo. 6. Dissemination and training campaigns were carried out on the services provided by the Free Legal Office of the University of Otavalo. In addition, an additional lawyer was hired for and the infrastructure was expanded, with individualized work cubicles for each student, as well as guaranteed in universal access for disabled people, adapting the ramps, the bathrooms and establishing better care policies for users.